Incidence of Duchenne muscular dystrophy in New South Wales and Australian Capital Territory. Issue 4 (August 1980) - Cowan, J; Macdessi, J; Stark, A; Morgan, G
Abstract : A survey was conducted during 1977 to 1978 to determine the incidence of Duchenne muscular dystrophy in New South Wales and the Australian Capital Territory. Ninety-nine cases born between 1960 and 1971 were ascertained representing an incidence rate of 18.6 per 100 000 liveborn males. Over 60% of the ascertained males were isolated cases, and only 7% of affected males had an affected males relative in a previous generation in the female line. Categorisation of ascertained cases as either "theoretically preventable" or not shows that genetic counselling alone in the present circumstances is insufficient to reduce the incidence rate significantly.